A label-free electrochemical immunosensor for rapid detection of salmonella in milk by using CoFe-MOFs-graphene modified electrode. (December 2021) - Feng, Kaiwen; Li, Ting; Ye, Cuizhu; Gao, Xiaoyu; Yang, Tan; Liang, Xuehua; Yue, Xianglin; Ding, Shuangyan; Dong, Qiuling; Yang, Mingqi; Xiong, Chunhong; Huang, Ganhui; et al.
Abstract: The presence of Salmonella in food has been a serious threat to human health all over the world. Herein, a novel electrochemical immunosensor based on CoFe-MOFs-graphene nanocomposite was constructed to detect Salmonella in milk. The synergy of the large specific surface area and high porosity of CoFe-MOFs and the good electrical conductivity of graphene materials greatly enhanced the current signal of the nanocomposite. Gold nanoparticles were modified on CoFe-MOFs-graphene hybrids by a simple electrodeposition method. Anti- Salmonella antibody was immobilized onto the surface of the constructed electrode through the formation of a stable Au–NH2 bond. Scanning electron microscopy was employed to reveal the structure of the CoFe-MOFs-graphene nanocomposite, and the elements of the nanocomposite were observed by energy-dispersive X-ray spectroscopy. In addition, Fourier transform infrared (FT-IR) and X-ray powder diffraction (XRD) were used to analyze the structure of related materials. Under optimal experimental parameters, the constructed immunosensor detected a wide linear range of Salmonella from 2.4 × 10 2 CFU mL −1 to 2.4 × 10 8 CFU mL −1 with a detection limit of 1.2 × 10 2 CFU mL −1 (S/N = 3). The immunosensor showed good stability, selectivity, and reproducibility. The designed immunosensor provides a new strategy for the rapid detection of foodborne pathogens. Highlights: The synergistic effect of graphene and CoFe-MOFs greatly improves the sensitivity of detection. AuNPs can form stable Au–NH2 with the amino group on the antibody. Electrochemical immunosensor can achieve rapid and sensitive detection of the target. Electrochemical method is easy to operate and provides a platform for others bacteria detection.